Medulloblastoma: Intraventricular Recurrences - Setiawan, Hendy; Wijaya, Celia; Dharmajaya, Ridha (Talenta Universitas Sumatera Utara, 2019)
Abstract :Medulloblastoma is the most common malignant pediatric brain tumor. Incidence in adult population is less than 1 %. Medulloblastoma in adult usually between 20 and 40 years old, which is lateral hemispheric and not midline vermian. Survival rate in adult is 67% lower than adolescents is 69% and children is 72%. Location of recurrences most commonly presents at posterior fossa, spinal, supratentorial, and bone metastases. Recurrences of medulloblastoma in supratentorial ventricular is uncommon. The outcome for patients with recurrent medulloblastoma has historically been poor. 37 years old male who presented with severe headache gradually. Patient has history of headache 2 months ago and gait ataxia 1,5 months ago. Patient had surgery 2 years ago with result of hystopathology medulloblastoma. He had irradiation completely 22 months ago. Physical examination showed GCS 15 with gait ataxia. Head CT scan show multiple isodense lesion intraventricular. Before patient had surgery, Head CT scan showed hiperdense lesion at cerebellopontine angle. Seeding medulloblastoma to intraventricular is recurrences which have poor prognosis. Patient had poor condition in few days. Patient died before got reriradiation